Obtenção de RNA odontoblástico de alta qualidade após o armazenamento de dentes em diferentes condições de temperatura - Conde, Marcus Cristian Muniz (2010)
Isolate high quality RNA form dental tissues is a most critical step to perform gene expression analysis. In some situations it is impossible to achieve the RNA isolation after tooth extraction, which leads to tooth discarding. Since, the aim of this experiment was to verify the effect of different teeth storage methods in the quality of RNA obtained from freshly extracted third molars. The teeth were randomly divided in five groups according to the temperature and storage time conditions. In control group RNA was isolated immediately after tooth extraction in room temperature. Experimental storage conditions evaluated were: liquid nitrogen, -80°C, -20°C (24h) and 4°C (6h). To RNA isolation, teeth were longitudinally sectioned and then pulp and pre-dentin were submerged in TRIzol®. Semi-quantitative RT-PCR was used to analyze the expression of odontoblast makers (DSPP, DMP1, and MEPE), which were normalized against the GAPDH gene. DSPP, DMP1 and MEPE were amplified in all storage conditions evaluated, regardless of storage method or tissue analyzed. Was possible to obtaining high quality RNA from pulp and dentin in all storage conditions appraised, increasing the RNA available to be used as positive control in cell differentiation studies